The performance test of plucking machine type 120 at plucking of assamica tea - Abbas, Tajudin (Research Institute for Tea and Cinchona, 2013)
The rate of increase tea cost production in several tea fields could not be offered by the rate of increase selling price. The fact that the cost of plucking machine is lower than manual plucking has attracted the interest and attention of tea smallholder to change from manual plucking to plucking machine. The plucking machine which were imported from japan was not designed for assamica tea in Indonesia. In order to improving performance of plucking machine, the plucking machine need to be designed with support from the field and Â appropriate machine. The aim of this trial was to test the performance of the plucking machine type-120 at plucking of assamica tea with 120 cm of spacing between rows. The plucking type used was medium plucking and kept the Kepel leaves (k +0) in the middle of the bushes using plucking method supported by the garden and the appropriate plucking machine type-120. Results obtained from the test were: (1) The using of plucking machine type-120 with medium plucking, kept the Kepel leaves (k +0), and controlled plucking height did not cause a decrease in plant health, production as well as quality of the shoots. (2) Field work capacity of plucking machine was 1.19 ha/day with work efficiency of 58.2%. (3) The ratio of plucking machine was 0.30/ha with fuel ratio of 0.33 litres/ha. The performance output of the plucking machine could be reached 224 kg/plucker as compared to only 24 kg/plucker when done manually.